Hubungan Stres Kerja dengan Kejenuhan Kerja (Burnout) pada Perawat Instalasi Gawat Darurat di RSUD Manembo-Nembo Bitung - Siti Nurhalisa Hasim; Silvia D. Mayasari Riu; Faradilla M. Suranata (Universitas Muhammadiyah Manado, 2024)
Burnout occurs because prolonged work stress is inevitable by nurses in carrying out their duties in serving patients in the hospital, the purpose of this study is to find out the relationship of work stress with work saturation (burnout) in emergency installation nurses at Manembo-Nembo Bitung Hospital. The study uses descriptive analytics methods with cross-sectional approaches. Sample is taken based on population of 40 respondents using total sampling method. The data collection is done using questionnaires as research instruments. The collected data was analyzed using a chi-square statistical test with alpha (α) ≤ 0.05. The results showed that nurses’ work stress was mostly in the weight category of 23 respondents (57.5%) and Burnout was as large as categorical as not occurring and occurred at 20 respondents (50.0%), with Chi-square test resulting in p-value=0,000, where p values are smaller than the value (α). The conclusion on the study there is a working stress relationship with work saturation (burnout) in the nurse of the installation of the department at Manembo-Nembo Bitung Hospital. It is recommended that you make an agenda or activities that are entertaining periodically for nurses so that nurses are not saturated and experience stress due to their work.